2020
DOI: 10.29271/jcpsp.2020.03.330
|View full text |Cite
|
Sign up to set email alerts
|

Presentations and Outcomes of Thyroid Storm

Abstract: The aim of this study is to describe the characteristics and outcome of thyroid storm patients presenting at two tertiary care centres of Karachi, i.e.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 2 publications
2
5
1
Order By: Relevance
“…The descriptive statistics showed that the wife’s self-rated depression score was 1.03 points higher than that of the husband, and the score of marital satisfaction and neurotic personality were similar between the husband and wife. Consistent with the results of two studies conducted in Poland [ 42 ] and Pakistan [ 43 ], wives are more depressed and dissatisfied with marriage than husbands. The same research results were reported in a study by Peterson et al [ 44 ].…”
Section: Discussionsupporting
confidence: 88%
“…The descriptive statistics showed that the wife’s self-rated depression score was 1.03 points higher than that of the husband, and the score of marital satisfaction and neurotic personality were similar between the husband and wife. Consistent with the results of two studies conducted in Poland [ 42 ] and Pakistan [ 43 ], wives are more depressed and dissatisfied with marriage than husbands. The same research results were reported in a study by Peterson et al [ 44 ].…”
Section: Discussionsupporting
confidence: 88%
“…Multisystem dysfunction of the cardiovascular system, thermoregulatory system, gastrointestinal-hepatic system, and central nervous system are common, and the Burch-Wartofsky scoring system is often used to standardize the diagnosis [ 1 , 4 ]. Our patient’s presentation corresponded with the classic clinical presentation of thyroid storm [ 5 ], which includes altered mentation, hyperpyrexia, tachycardia, nausea, and vomiting. However, in the absence of a history of hyperthyroidism, sepsis was considered as the most likely cause, and further testing was only initiated after the workup for sepsis was negative.…”
Section: Discussionsupporting
confidence: 62%
“…Presently, diabetes mellitus has become a major health issue. By 2035, about 592 million people would be diabetic patients, which will be 210 million higher than reported in 2013 (Shahid et al, 2016). Every year, the number of people affected by this lifelong health problem is increasing.…”
Section: Introductionmentioning
confidence: 92%